Chromium-site high-entropy chromium lithium titanate material as well as preparation method and application thereof
By introducing multiple metal elements into lithium chromium titanate to construct a high-entropy solid solution and employing a combustion synthesis process, the capacity and rate performance issues of lithium chromium titanate were solved, achieving efficient material modification and a simplified preparation process.
Patent Information
- Application Number
- CN202511938022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-01-16
- Estimated Expiration
- 2045-12-22
AI Technical Summary
Existing lithium chromium titanate materials have limited theoretical specific capacity and poor rate performance, and current modification studies are insufficient to improve overall performance.
High-entropy lithium chromium titanate material with chromium sites is prepared by introducing multiple metal elements such as iron, aluminum, vanadium, and manganese into chromium lattice sites in near equimolar ratios to construct a high-entropy solid solution with a single spinel structure. The high-entropy solid solution is then prepared using an efficient combustion synthesis process, resulting in a highly crystalline high-entropy lithium chromium titanate material with chromium sites.
It significantly improves the lithium storage capacity and cycle stability of the material, reduces synthesis time and energy consumption, and has good potential for industrial application.
Smart Images

Figure CN121342087A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage materials technology, and relates to a high-capacity lithium chromium titanate anode material for lithium-ion batteries, specifically a chromium-site high-entropy lithium chromium titanate material, its preparation method, and its application. Background Technology
[0002] With the rapid development of portable electronic devices, electric vehicles, and large-scale energy storage grids, the market demand for lithium-ion batteries that combine high energy density, high power density, long cycle life, and high safety is becoming increasingly urgent. As a core component of lithium-ion batteries, the performance of the anode material directly determines the overall performance of the battery. Currently, commercial lithium-ion batteries mainly use graphite-based carbon materials as the anode. While these materials have advantages in cost and process maturity, their operating potential is close to the deposition potential of metallic lithium, posing a safety risk of lithium dendrite formation during overcharging, leading to short circuits and thermal runaway. Furthermore, their low initial coulombic efficiency and poor compatibility with some electrolytes also limit their application in high-performance batteries.
[0003] Spinel-type lithium titanate (Li4Ti5O) 12 Lithium-ion peroxide (LTO) exhibits near-zero strain during lithium-ion insertion / extraction, resulting in ultra-long cycle life and excellent safety, making it a promising anode material. However, LTO has extremely low intrinsic electronic conductivity (approximately 10⁻⁶ ppm). -13 Its low density (S / cm) and small lithium-ion diffusion coefficient result in poor rate performance, making it difficult to meet the demands of high-power charging and discharging. Furthermore, its relatively limited theoretical specific capacity (approximately 175 mAh / g) also restricts further improvements in battery energy density. Therefore, developing novel anode material systems has become an important research direction in the industry.
[0004] In contrast, lithium chromium titanate (LiCrTiO4, LCT) with the same spinel structure exhibits intrinsic electronic conductivity superior to that of LTO while maintaining similar "zero-strain" characteristics and high safety, making it more promising for high-rate applications. Existing modification studies on LCT mostly draw on the relatively mature experience of LTO, but the overall research depth and breadth are limited, and the ideas are relatively traditional. Existing research mainly focuses on traditional element doping or surface composite / capping. For example, single elements (such as Cr, Al) are introduced for doping to optimize the intrinsic conductivity or voltage platform of the material, or composite with carbon materials or other active substances to construct a conductive network. However, the optimization effect of single-element doping has an upper limit, often only improving a certain performance index of the material and being difficult to achieve synchronous improvement of comprehensive performance. And simple surface capping can improve interfacial kinetics but cannot fundamentally solve the problem of insufficient intrinsic lithium storage capacity of the material. In addition, existing synthesis methods of LCT, such as high-temperature solid-phase method, sol-gel method, etc., generally have problems such as complex process flow, long reaction time, high energy consumption or high cost, which are not conducive to large-scale industrial application.
[0005] In summary, the current modification research on LCT anode materials has not made breakthrough progress in improving its intrinsic specific capacity, and existing methods are difficult to achieve improvement of the comprehensive performance of the material (such as capacity, rate, structural stability).
[0006] Therefore, there is an urgent need for a method that can simultaneously improve the comprehensive performance of LCT materials and has a simple process and is easy to industrialize. SUMMARY OF THE INVENTION
[0007] The technical problem to be solved by this invention is the problem of limited theoretical specific capacity and poor rate performance of existing lithium chromium titanate materials.
[0008] To achieve the above application objectives, the technical solutions adopted in this application are as follows.
[0009] In the first aspect, the present invention provides a chromium-site high-entropy lithium chromium titanate (abbreviated as CrHELCT) material. The crystal structure of the chromium-site high-entropy lithium chromium titanate material is a single spinel solid solution phase, and its chemical general formula is Li(Cr 1-x-y-z-w V x Fe y [[ID=e3]]Mn z Al w )TiO4; Among them, x, y, z, w satisfy 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, 0 < w ≤ 0.1 and 0 < x + y + z + w ≤ 0.5.
[0010] Furthermore, the configurational entropy of the aforementioned high-entropy lithium chromium titanate material at the chromium site is greater than 1.3R; Where R is the gas constant, with a value of 8.314 J / (mol·K).
[0011] Secondly, the present invention provides a method for preparing the above-mentioned chromium-site high-entropy lithium chromium titanate material, comprising the following steps: S1. Weigh out chromium source, titanium source, lithium source, vanadium source, iron source, manganese source and aluminum source according to the stoichiometric ratio of the above general chemical formula, mix them with carbohydrates and grind them to form a precursor; The chromium source is chromium trioxide (CrO3), and the number of carbon atoms in the carbohydrate is 2 to 6 times the number of chromium atoms in the chromium source. S2. The precursor is transferred to an open high-temperature resistant container and then placed in a reaction apparatus that has been preheated to the set temperature. It is fully combusted in an air atmosphere. After the reaction is completed, it is air-cooled to room temperature to obtain chromium-site high-entropy lithium chromium titanate material. The set temperature is 750~950℃.
[0012] In step S1 above, the number of carbon atoms in the carbohydrate is 2 to 3 times the number of chromium atoms in the chromium source.
[0013] In step S1 above, the titanium source is at least one of titanium dioxide, titanium oxysulfate, and tetrabutyl titanate.
[0014] In step S1 above, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium chloride.
[0015] In step S1 above, the vanadium source is at least one of vanadium pentoxide, ammonium metavanadate, and vanadium oxysulfate.
[0016] In step S1 above, the iron source is at least one of ferric oxide, ferrous sulfate, and ferric sulfate.
[0017] In step S1 above, the manganese source is at least one of manganese dioxide, manganese sulfate, and manganese acetate.
[0018] In step S1 above, the aluminum source is at least one of aluminum oxide, aluminum sulfate, and aluminum chloride.
[0019] In step S1 above, the carbohydrate is at least one of glucose, sucrose, and starch.
[0020] In step S1 above, an appropriate amount of liquid medium is added during grinding until the mixture forms a uniform, non-flowing paste-like precursor. The liquid medium is polyethylene glycol 400 (PEG400), or polyethylene glycol 400 and water.
[0021] In step S2 above, the amount of the precursor is 1 / 4 to 3 / 4 of the volume of the open high-temperature resistant container.
[0022] In step S2 above, the combustion reaction begins timing after the temperature inside the reaction device recovers to the set temperature, and the time is 30 to 360 minutes.
[0023] In step S2 above, the set temperature is 800℃.
[0024] Thirdly, the present invention provides the application of the above-mentioned chromium-site high-entropy lithium chromium titanate material, or the chromium-site high-entropy lithium chromium titanate material prepared by the above preparation method, in lithium-ion batteries.
[0025] The beneficial effects of this invention are as follows: This invention provides a method for modifying lithium chromium titanate (LCT) materials through "chromium-site high-entropy modification." This method overcomes the limitations of traditional single or dual-element doping. By synergistically introducing multiple metal elements such as iron (Fe), aluminum (Al), manganese (Mn), and vanadium (V) into the chromium (Cr) lattice sites of LCT in a near equimolar ratio, a highly entropy solid solution with a single spinel structure and good crystallinity—that is, chromium-site high-entropy LCT material—is successfully constructed. The high-entropy modification strategy employed in this invention synergistically optimizes the electronic structure and ion transport kinetics of the material, resulting in a significant improvement in lithium storage capacity compared to unmodified LCT, and exhibiting excellent cycle stability and structural reversibility at lower rates. Simultaneously, the combustion synthesis process utilizes a highly efficient self-propagating reaction, significantly shortening the synthesis time, reducing energy consumption and process complexity, demonstrating good potential for industrial application, and providing an effective technical path for developing novel high-performance lithium-ion battery anode materials. Attached Figure Description
[0026] Figure 1 The XRD pattern of the high-entropy lithium chromium titanate material prepared in Example 1 is shown. Figure 2 The discharge specific capacity diagram of the chromium-site high-entropy lithium chromium titanate material prepared in Example 1 at a 1C rate; Figure 3 The XRD pattern of the high-entropy lithium chromium titanate material prepared in Example 2 is shown. Figure 4 SEM image of the chromium-site high-entropy lithium chromium titanate material prepared in Example 2; Figure 5 The XRD pattern of the high-entropy lithium chromium titanate material prepared in Example 3 is shown. Figure 6 The XRD pattern of the high-entropy lithium chromium titanate material prepared in Example 4 is shown. Figure 7 XRD pattern of the chromium-site high-entropy lithium chromium titanate material prepared in Example 5; Figure 8 Discharge specific capacity diagram of the chromium-site high-entropy lithium chromium titanate material prepared in Example 5 at different rates; Figure 9 XRD pattern of the chromium-site high-entropy lithium chromium titanate material prepared in Example 6; Figure 10 Discharge specific capacity diagram of the chromium-site high-entropy lithium chromium titanate material prepared in Example 6 at different rates; Figure 11 XRD pattern of the lithium chromium titanate material prepared in Comparative Example 1; Figure 12 Discharge specific capacity diagram of the lithium chromium titanate material prepared in Comparative Example 1 at different rates; Figure 13 XRD pattern of the lithium chromium titanate material prepared in Comparative Example 2. Detailed implementation manners
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer and more understandable, the present application will be further described in detail below in conjunction with the implementation manners. Unless otherwise defined, all technical terms used herein have the same meaning as understood by those of ordinary skill in the art.
[0028] The present invention provides a CrHELCT material and its high-entropy modification method. The crystal structure of the CrHELCT material is a single spinel solid solution phase, and its chemical general formula is Li(Cr 1-x-y-z-w V x Fe y Mn z Al w )TiO4; wherein, the molar fractions x, y, z, w of each element satisfy: 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, 0 < w ≤ 0.1 and 0 < x + y + z + w ≤ 0.5.
[0029] LCT exhibits a "zero-strain" characteristic similar to LTO, and its conductivity is better than LTO, but its electrochemical specific capacity is slightly smaller. To improve the electrochemical capacity and overall electrochemical performance of LCT, this invention proposes a "chromium-site high-entropy" modification method to prepare CrHELCT materials. The modification method of this invention uses LCT as a matrix and constructs a multi-principal-element high-entropy solid solution by synergistically introducing Fe, V, Mn, and Al into Cr sites in a specific ratio. The introduction of Fe and V aims to synergistically improve the material's reversible capacity and electronic conductivity; the introduction of Mn and Al is mainly used to stabilize the spinel structure. The combination of Fe, V, Mn, Al, and Cr in LCT produces a high-entropy effect. Through a strong "cocktail" synergistic effect and lattice distortion, the elements synergistically regulate the electronic structure and lithium-ion transport kinetics of the material, thereby significantly improving the electrochemical performance of the LCT material and resulting in a significant improvement in the overall electrochemical performance of the obtained CrHELCT material.
[0030] The CrHELCT material of this invention is prepared by a one-step combustion synthesis method based on the principle of self-propagating combustion. Its core lies in using CrO3 as the chromium source and oxidant, and carbohydrates as the reducing agent, to form a rapid and efficient redox reaction system, thereby modifying LCT through high entropy modification of Cr sites. The preparation method of the CrHELCT material specifically includes the following steps.
[0031] Step 1, Precursor Preparation: Accurately weigh the chromium source, titanium source, lithium source, vanadium source, iron source, manganese source, and aluminum source according to the stoichiometric ratio of the target product's chemical formula. Place the weighed solid metal raw materials and carbohydrate reducing agent together in a mortar, add an appropriate amount of liquid medium including PEG400, and grind thoroughly until the mixture forms a uniform, non-flowing paste-like precursor.
[0032] In one embodiment of the present invention, the chromium source is CrO3; the titanium source is at least one of titanium dioxide, titanium oxysulfate, and tetrabutyl titanate; the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium chloride; the vanadium source is at least one of vanadium pentoxide, ammonium metavanadate, and vanadium oxysulfate; the iron source is at least one of ferric oxide, ferrous sulfate, and ferric sulfate; the manganese source is at least one of manganese dioxide, manganese sulfate, and manganese acetate; the aluminum source is at least one of alumina, aluminum sulfate, and aluminum chloride; and the carbohydrate is at least one of glucose, sucrose, and starch. The role of CrO3 is not only to provide chromium, but more importantly, as a strong oxidizing agent, it decomposes at high temperatures to release oxygen and provide the heat required to initiate the reaction, which is the foundation of the combustion reaction system. If other chromium sources (such as Cr2O3) are used, sufficient oxidation potential energy and instantaneous heat cannot be provided, resulting in the combustion reaction failing to occur or proceeding incompletely.
[0033] In one embodiment of the present invention, the number of carbon atoms in the carbohydrate is 2 to 6 times the number of chromium atoms in the chromium source. The amount of reducing agent added is crucial for controlling the intensity of the combustion reaction and the purity of the product. An appropriate amount of carbon acts as a reducing agent, reacting violently with the oxygen released from the decomposition of CrO3, providing most of the heat required for the synthesis reaction, and providing a strong reducing atmosphere to promote the reduction of various metal oxides and their mutual reaction to form a spinel phase. If the C:Cr atomic molar ratio is too low, unreacted CrO3 may remain or high-valence impurities may be present in the product; if the ratio is too high, the reaction is too violent and difficult to control, and excessive free carbon may remain after combustion, requiring a longer subsequent oxidation time to remove it completely, and potentially affecting the purity and performance of the product. To ensure a sufficient and rapid reaction while achieving optimal energy utilization and product quality control, it is preferable that the number of carbon atoms in the carbohydrate is 2 to 3 times the number of chromium atoms in the chromium source.
[0034] Those skilled in the art will understand that one of the core aspects of step one of the present invention lies in the final generation of Li(Cr) conforming to the target chemical formula. 1-x-y-z-w V x Fe y Mn z Al w The material is TiO4. Therefore, the weighing of each raw material should be based on its stoichiometric relationship in the general formula. In actual high-temperature combustion synthesis processes, some raw materials (especially lithium-containing compounds) may volatilize or burn off in small amounts during the intense combustion reaction and subsequent heat preservation process. To ensure that the stoichiometric ratio of the final product is as close as possible to the theoretical design value, those skilled in the art usually add an appropriate excess of the volatile components during the batching process according to the properties of the selected specific raw materials, reaction temperature, and time. This is a common and necessary process compensation method in the art. For example, in a specific embodiment of the present invention, Li:(Cr) is used. 1-x-y-z-w V x Fe y Mn z Al w The raw material molar ratio of Ti is 1.1:1:1. The lithium content is approximately 10% in excess compared to the theoretical value to compensate for potential lithium loss at high temperatures, thus ensuring the actual lithium content in the product. The amounts of total chromium metals (Cr, V, Fe, Mn, Al) and Ti are strictly in accordance with the theoretical stoichiometric ratio in the general formula. This adjustment of the raw material amounts to achieve the target chemical composition, which conforms to common knowledge in the art, does not deviate from the core limitation of this invention—the formulation based on the stoichiometric relationship of the general formula—and falls within the scope of protection of this invention.
[0035] Those skilled in the art will understand that the core of step one of this invention lies in obtaining a precursor with a specific physical state through grinding, namely, ensuring that the final material is a uniform, non-flowing paste. The scope of protection for the grinding step is not limited to the specific operating parameters and feeding sequence given in the embodiments. In actual process implementation, as long as the above core objective can be achieved, those skilled in the art can routinely adjust and optimize parameters such as grinding time, type and amount of liquid medium, and the order of addition of each raw material according to the actual material properties. For example, in a specific embodiment of this invention, one can choose to first mix and grind the metal raw material with a portion of the liquid medium to a paste-like state, and then add a reducing agent and the remaining liquid medium for further mixing; or adopt stepwise grinding and batch liquid addition methods. Any routine adjustments or equivalent substitutions made to this technical solution without departing from the core concept of this invention, namely, ultimately forming a uniform, non-flowing paste-like precursor, should be covered within the scope of protection of this invention.
[0036] Step two, combustion synthesis reaction: The paste-like precursor obtained in step one is transferred to an open, high-temperature resistant container (such as a corundum crucible). The container containing the material is then quickly placed into a reaction apparatus (such as a muffle furnace) preheated to the target temperature of 750~950℃. The precursor is rapidly ignited in a high-temperature environment (air atmosphere), resulting in a violent combustion reaction. After the reaction is complete, the product is naturally cooled to room temperature in air atmosphere, yielding a loose, porous, foam-like solid. Grinding this solid yields a spinel-type chromium-site high-entropy lithium chromium titanate material powder with uniform particle size.
[0037] In one embodiment of the invention, the precursor is packed in a volume of approximately 1 / 4 to 3 / 4 of the open high-temperature resistant container. If the amount packed is too small, the thermal effect will be weak, and the reaction may not be self-sustaining; if the amount packed is too large, the reaction may be too violent, material may splash, or excessive heat may accumulate, affecting the morphology of the product.
[0038] In one embodiment of the present invention, the combustion reaction temperature is 750~950℃. If the temperature is too low, the precursor may not be ignited, leading to difficulty in initiating the combustion reaction or a slow reaction rate, making it impossible to utilize the self-propagating properties and resulting in poor product crystallinity. If the temperature is too high, the reaction degree is difficult to control, which may lead to the volatilization and loss of some low-boiling-point components, abnormal grain growth, and is therefore detrimental to obtaining materials with excellent performance. Preferably, the combustion reaction temperature is 800℃, at which temperature the product obtained has good crystallinity and ideal particle morphology.
[0039] In one embodiment of the invention, the combustion reaction is timed after the muffle furnace temperature recovers to the set temperature, and the holding time is 30-360 minutes. The purpose of holding the temperature is to promote atomic diffusion, ensure the formation of a thermodynamically stable single spinel phase, and obtain sufficient crystallinity.
[0040] This invention also provides the application of the above-mentioned chromium-site high-entropy lithium chromium titanate material in lithium-ion batteries. This material exhibits high specific capacity and good cycle stability at lower rates, making it particularly suitable for applications with high requirements for energy density and cycle life, such as energy storage.
[0041] To adapt this material to a wider range of applications (such as high-rate charge and discharge), those skilled in the art can perform secondary processing using conventional techniques. For example, a conductive carbon layer can be formed on the surface of the material particles through conventional carbon source coating and heat treatment processes, or the particle size and morphology can be controlled through conventional nano-sizing processes to improve its discharge specific capacity and cycle stability at high rates, thereby further optimizing its electrochemical performance.
[0042] Those skilled in the art will understand that secondary treatments of the chromium-site high-entropy lithium chromium titanate material of the present invention, such as surface coating with a conductive carbon layer and particle size control, are conventional optimization methods for its application in specific lithium-ion battery devices. These subsequent treatments are all based on and predicated on the CrHELCT material with the specific chemical composition and crystal structure provided by the present invention. Therefore, regardless of whether such conventional optimizations have been performed, or what specific type of battery device it is applied to, as long as its active material components include the CrHELCT material described in the present invention, it should be considered within the scope of protection of the present invention.
[0043] The following specific embodiments will be provided to explain the solution of the present invention. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0044] Example 1: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.84 V 0.03 Fe 0.02 Mn 0.05 Al 0.06 TiO4, the specific steps are as follows.
[0045] (1) Using CrO3 as the chromium source and oxidant, titanium dioxide as the titanium source, lithium carbonate as the lithium source, ammonium metavanadate as the vanadium source, ferric oxide as the iron source, manganese dioxide as the manganese source, aluminum oxide as the aluminum source, and glucose as the reducing agent. According to Li:(Cr 0.84 V 0.03 Fe 0.02 Mn 0.05 Al 0.06Weigh each raw material in a molar ratio of Ti = 1.1:1:1, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 2:1 (i.e., the number of carbon atoms in the reducing agent is twice the number of chromium atoms in the chromium source).
[0046] (2) Mix the raw materials except for the reducing agent, add an appropriate amount of deionized water and grind for 15 minutes, add the reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 3% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0047] (3) Transfer the precursor to an open corundum crucible (filling approximately 1 / 2 full) and place it in a muffle furnace preheated to 750°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 750°C, maintain the temperature for 360 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.84 V 0.03 Fe 0.02 Mn 0.05 Al 0.06 )TiO4 powder.
[0048] The obtained Li(Cr) 0.84 V 0.03 Fe 0.02 Mn 0.05 Al 0.06 The configurational entropy of TiO4 material is approximately 1.315R (R is the gas constant, with a value of 8.314 J / mol·K), indicating that it has successfully achieved high entropy. XRD pattern ( Figure 1 The results showed that all diffraction peaks matched the spinel structure standard card, with no impurity phase peaks, indicating that the product is a well-crystallized pure spinel phase. Electrochemical tests showed that its initial discharge specific capacity at 0.1C rate was 168 mAh / g; its capacity retention after 100 cycles at 1C rate was 100%. Figure 2 It exhibits excellent cycle stability.
[0049] Example 2: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.5 V 0.2 Fe 0.1 Mn 0.1 Al 0.1 TiO4, the specific steps are as follows.
[0050] (1) Using CrO3 as the chromium source and oxidant, tetrabutyl titanate as the titanium source, lithium acetate as the lithium source, ammonium metavanadate as the vanadium source, ferrous sulfate as the iron source, manganese acetate as the manganese source, aluminum sulfate as the aluminum source, and sucrose as the reducing agent. According to Li:(Cr 0.5 V 0.2 Fe 0.1 Mn0.1 Al 0.1 Weigh each raw material in a molar ratio of 1.1:1:1 for Ti, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 4:1.
[0051] (2) Mix and grind CrO3, ammonium metavanadate, ferrous sulfate and aluminum sulfate for 15 minutes, add tetrabutyl titanate, lithium acetate and manganese acetate and grind for 15 minutes, add reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 1% of the total solid mass and an appropriate amount of deionized water and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0052] (3) Transfer the precursor to an open corundum crucible (filling approximately 1 / 3 full) and place it in a muffle furnace preheated to 800°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 800°C, maintain the temperature for 180 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.5 V 0.2 Fe 0.1 Mn 0.1 Al 0.1 )TiO4 powder.
[0053] The obtained Li(Cr) 0.5 V 0.2 Fe 0.1 Mn 0.1 Al 0.1 The configuration entropy of TiO4 material is approximately 1.552R. (XRD pattern) Figure 3 The SEM image shows that it is a well-crystallized pure spinel phase. Figure 4 The results show that its grains are well-grown and densely packed, with an average grain size of about 1 micrometer. Electrochemical tests indicate that its initial discharge specific capacity at 0.1C rate is 268 mAh / g.
[0054] Example 3: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.7 V 0.15 Fe 0.1 Mn 0.025 Al 0.025 TiO4, the specific steps are as follows.
[0055] (1) Using CrO3 as the chromium source and oxidant, titanium dioxide as the titanium source, lithium hydroxide as the lithium source, vanadium pentoxide as the vanadium source, ferric oxide as the iron source, manganese dioxide as the manganese source, aluminum chloride as the aluminum source, and starch as the reducing agent. According to Li:(Cr 0.7 V 0.15 Fe 0.1 Mn 0.025 Al 0.025Weigh each raw material in a molar ratio of Ti = 1.1:1:1, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 6:1.
[0056] (2) Mix the raw materials except for the reducing agent, add an appropriate amount of deionized water and grind for 15 minutes, add the reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 5% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0057] (3) Transfer the precursor to an open corundum crucible (filled to approximately 2 / 3 capacity) and place it in a muffle furnace preheated to 950°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 950°C, maintain the temperature for 30 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.7 V 0.15 Fe 0.1 Mn 0.025 Al 0.025 )TiO4 powder.
[0058] The obtained Li(Cr) 0.7 V 0.15 Fe 0.1 Mn 0.025 Al 0.025 The configuration entropy of TiO4 material is approximately 1.415R. (XRD pattern) Figure 5 The sample showed that it was a highly crystalline pure spinel phase. Electrochemical tests showed that its initial discharge specific capacity at 0.1C rate was 225 mAh / g.
[0059] Example 4: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.55 V 0.15 Fe 0.1 Mn 0.1 Al 0.1 TiO4, the specific steps are as follows.
[0060] (1) Using CrO3 as the chromium source and oxidant, titanium dioxide as the titanium source, lithium chloride as the lithium source, vanadium pentoxide as the vanadium source, ferric oxide as the iron source, manganese dioxide as the manganese source, aluminum oxide as the aluminum source, and glucose and starch (mixed in a 1:1 mass ratio) as the reducing agent. According to Li:(Cr 0.55 V 0.15 Fe 0.1 Mn 0.1 Al 0.1 Weigh each raw material in a molar ratio of 1.1:1:1 for Ti, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 4:1.
[0061] (2) Mix the raw materials except for the reducing agent, add an appropriate amount of deionized water and grind for 15 minutes, add the reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 4% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0062] (3) Transfer the precursor to an open corundum crucible (approximately 1 / 3 full) and place it in a muffle furnace preheated to 800°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 800°C, maintain the temperature for 120 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.55 V 0.15 Fe 0.1 Mn 0.1 Al 0.1 )TiO4 powder.
[0063] The obtained Li(Cr) 0.55 V 0.15 Fe 0.1 Mn 0.1 Al 0.1 The configuration entropy of TiO4 material is approximately 1.533R. (XRD pattern) Figure 6 The sample showed that it was a highly crystalline pure spinel phase. Electrochemical tests showed that its initial discharge specific capacity at 0.1C rate was 252 mAh / g.
[0064] Example 5: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.6 V 0.1 Fe 0.2 Mn 0.05 Al 0.05 TiO4, the specific steps are as follows.
[0065] (1) Using CrO3 as the chromium source and oxidant, titanium dioxide as the titanium source, lithium carbonate as the lithium source, ammonium metavanadate as the vanadium source, ferric sulfate as the iron source, manganese sulfate as the manganese source, aluminum sulfate as the aluminum source, and starch as the reducing agent. According to Li:(Cr 0.6 V 0.1 Fe 0.2 Mn 0.05 Al 0.05 Weigh each raw material in a molar ratio of 1.1:1:1 for Ti, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 4:1.
[0066] (2) Mix CrO3, titanium dioxide, lithium carbonate, ammonium metavanadate, ferric sulfate and aluminum sulfate, add an appropriate amount of deionized water and grind for 15 minutes, add manganese sulfate and grind for 5 minutes, add reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 3% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0067] (3) Transfer the precursor to an open corundum crucible (approximately 1 / 3 full) and place it in a muffle furnace preheated to 850°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 850°C, maintain the temperature for 240 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.6 V 0.1 Fe 0.2 Mn 0.05 Al 0.05 )TiO4 powder.
[0068] The obtained Li(Cr) 0.6 V 0.1 Fe 0.2 Mn 0.05 Al 0.05 The configuration entropy of TiO4 material is approximately 1.485R. (XRD pattern) Figure 7 The results show that it is a well-crystallized pure spinel phase. Electrochemical tests show that its initial discharge specific capacity at 0.1C rate is 393 mAh / g; its discharge specific capacity at different rates is shown in the graph (). Figure 8 The results show that it can still maintain a discharge capacity of about 100mAh / g at a high 2C rate, and its capacity has basically not decreased after nearly 50 cycles at a 0.2C rate, demonstrating excellent cycle stability.
[0069] Example 6: Preparation of high-entropy lithium chromium titanate material with chromium site, its chemical formula is Li(Cr) 0.58 V 0.08 Fe 0.2 Mn 0.06 Al 0.08 TiO4, the specific steps are as follows.
[0070] (1) Using CrO3 as the chromium source and oxidant, titanium dioxide as the titanium source, lithium carbonate as the lithium source, ammonium metavanadate as the vanadium source, ferric oxide as the iron source, manganese dioxide as the manganese source, aluminum oxide as the aluminum source, and starch as the reducing agent. According to Li:(Cr 0.58 V 0.08 Fe 0.2 Mn 0.06 Al 0.08 Weigh each raw material in a molar ratio of Ti = 1.1:1:1, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 5:1.
[0071] (2) Mix the raw materials except for the reducing agent, add an appropriate amount of deionized water and grind for 15 minutes, add the reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 5% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0072] (3) Transfer the precursor to an open corundum crucible (filling approximately 1 / 2 full) and place it in a muffle furnace preheated to 950°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 950°C, maintain the temperature for 30 minutes. After the reaction is complete, air cool to room temperature, grind, and obtain Li(Cr) 0.58 V 0.08 Fe 0.2 Mn 0.06 Al 0.08 )TiO4 powder.
[0073] The obtained Li(Cr) 0.58 V 0.08 Fe 0.2 Mn 0.06 Al 0.08 The configuration entropy of TiO4 material is approximately 1.502R. (XRD pattern) Figure 9 The results show that it is a well-crystallized pure spinel phase. Electrochemical tests show that its initial discharge specific capacity at 0.1C rate is 314 mAh / g; its discharge specific capacity at different rates is shown in the graph (). Figure 10 The results show that it can still maintain a discharge capacity of about 125mAh / g at a higher 2C rate, and its capacity has basically not decreased after nearly 50 cycles at a 0.2C rate, demonstrating excellent cycle stability.
[0074] Comparative Example 1: Pure lithium chromium titanate material without high-entropy modification was prepared using the combustion method described in this invention. Its chemical formula is LiCrTiO4. The specific steps are as follows.
[0075] (1) Using CrO3 as the chromium source, titanium dioxide as the titanium source, lithium sulfate as the lithium source, and starch as the reducing agent. Weigh each raw material according to the molar ratio of Li:Cr:Ti=1.1:1:1, and control the atomic molar ratio of carbon in the reducing agent to chromium in the chromium source to be 6:1.
[0076] (2) Mix the raw materials except for the reducing agent, add an appropriate amount of deionized water and grind for 15 minutes, add the reducing agent and grind for 5 minutes, and finally add PEG400 accounting for 3% of the total solid mass and continue grinding for 5 minutes to form a uniform, non-flowing paste-like precursor.
[0077] (3) Transfer the precursor to an open corundum crucible (filled to about 1 / 2 capacity) and place it in a muffle furnace preheated to 850°C. The material undergoes a self-propagating combustion reaction. After the furnace temperature returns to 850°C, maintain the temperature for 60 minutes. After the reaction is complete, air cool to room temperature and grind to obtain LiCrTiO4 powder.
[0078] The configurational entropy of the obtained LiCrTiO4 material is approximately 1.099R, significantly lower than that of the high-entropy materials in the embodiments of this invention. (XRD pattern) Figure 11The results show that it is a pure spinel phase. Electrochemical tests show that its initial discharge specific capacity at 0.1C rate is 155 mAh / g; its discharge specific capacity at different rates is shown in the graph (). Figure 12 The results show that its discharge capacity at a relatively high 2C rate is only 60mAh / g, and after nearly 50 cycles at a 0.2C rate, the capacity decay is quite significant, indicating poor rate performance and cycle stability.
[0079] Comparative Example 2: Pure lithium chromium titanate material without high-entropy modification was prepared using the traditional high-temperature solid-state method. Its chemical formula is LiCrTiO4. The specific steps are as follows.
[0080] (1) Using CrO3 as the chromium source, titanium dioxide as the titanium source, and lithium hydroxide monohydrate as the lithium source, weigh each raw material according to the molar ratio of Li:Cr:Ti = 1.1:1:1.
[0081] (2) Mix the raw materials, add an appropriate amount of deionized water and grind for 20 minutes. Finally, add PEG400 accounting for 3% of the total solid mass and continue grinding for 10 minutes to form a uniform, non-flowing paste-like precursor.
[0082] (3) The precursor was transferred to an open corundum crucible (filled to about 2 / 3) and placed in a muffle furnace preheated to 800°C for calcination for 360 minutes. After the reaction was completed, the crucible was cooled to room temperature and ground to obtain LiCrTiO4 powder.
[0083] The obtained XRD pattern of LiCrTiO4 material ( Figure 13 The results indicate that it belongs to the spinel phase. Electrochemical tests show that its initial discharge specific capacity at 0.1C rate is only 137 mAh / g.
[0084] Comparing the test results of the examples and comparative examples, it can be seen that the pure-phase LCT synthesized using the combustion method of the present invention (Comparative Example 1) has a significantly higher initial discharge specific capacity than the product of the traditional solid-phase method (Comparative Example 2), indicating that the combustion method process of the present invention itself is beneficial to improving the basic performance of the material. Furthermore, under the same combustion process conditions, the electrochemical performance of the materials modified by "chromium-site high entropy" (Examples 1-6) is significantly better than that of the unmodified pure-phase LCT (Comparative Examples 1-2). This shows that the present invention, through the combination of "chromium-site high entropy" material design and combustion synthesis process, can synergistically improve the comprehensive electrochemical performance of LCT materials.
Claims
1. A chromium-site high-entropy chromium lithium titanate material, characterized in that: The crystal structure of the chromium-site high-entropy chromium lithium titanate material is a single spinel solid solution phase, and its chemical general formula is Li(Cr 1-x-y-z-w V x Fe y Mn z Al w )TiO4; Wherein, the x, y, z, w satisfy 0 < x ≤ 0.2, 0 < y ≤ 0.2, 0 < z ≤ 0.1, 0 < w ≤ 0.1 and 0 < x + y + z + w ≤ 0.
5.
2. The chromium-site high-entropy lithium chromatitanate material of claim 1, wherein: The configuration entropy of the chromium-site high-entropy lithium chromic titanate material is greater than 1.3R; wherein, R is a gas constant.
3. A method for preparing a chromium site high-entropy chromium lithium titanate material, characterized in that, The method comprises the following steps: S1. According to the stoichiometric ratio of the chemical formula, the chromium source, titanium source, lithium source, vanadium source, iron source, manganese source and aluminum source are weighed, mixed with a carbohydrate and ground to form a precursor; Wherein, the chromium source is chromium trioxide, and the atomic molar number of carbon elements in the carbohydrate is 2-6 times that of chromium elements in the chromium source; S2. The precursor is transferred to an open high-temperature resistant container, and then placed in a reaction device preheated to a set temperature, and then fully combusted in an air atmosphere, and then air-cooled to room temperature after the reaction to obtain a chromium-site high-entropy lithium chromic titanate material; Wherein, the set temperature is 750-950℃.
4. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: mixing a lithium source, a chromium source, a titanium source, and a metal source to form a mixture; and heating the mixture to form the chromium site high-entropy lithium chromite titanate material. In step S1, the atomic molar number of carbon elements in the carbohydrate is 2-3 times that of chromium elements in the chromium source.
5. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: mixing a lithium source, a chromium source, a titanium source, and a metal source to form a mixture; and heating the mixture to form the chromium site high-entropy lithium chromite titanate material. In step S1: The titanium source is at least one of titanium dioxide, titanyl sulfate, and tetrabutyl titanate; The lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium chloride; The vanadium source is at least one of vanadium pentoxide, ammonium metavanadate, and vanadyl sulfate; The iron source is at least one of ferrous sulfate, ferrous sulfate, and high-iron sulfate; The manganese source is at least one of manganese dioxide, manganese sulfate, and manganese acetate; The aluminum source is at least one of aluminum oxide, aluminum sulfate, and aluminum chloride; The carbohydrate is at least one of glucose, sucrose, and starch.
6. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: In step S1, the grinding is performed by adding an appropriate amount of liquid medium until the mixture forms a uniform, non-flowing paste-like precursor; The liquid medium is polyethylene glycol 400, or polyethylene glycol 400 and water.
7. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: In step S2, the loading amount of the precursor is 1 / 4-3 / 4 of the volume of the open high-temperature resistant container. 8. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: In step S2, the combustion reaction starts after the temperature in the reaction device recovers to the set temperature, and the time is 30-360 minutes. 9. The method of claim 3, wherein the chromium site high-entropy lithium chromite titanate material is prepared by the method comprising: In step S2, the set temperature is 800℃. 10. The chromium-site high-entropy lithium chromic titanate material of any one of claims 1-2, or the application of the chromium-site high-entropy lithium chromic titanate material prepared by the method of any one of claims 3-9 in a lithium ion battery.
Citation Information
Patent Citations
Preparation method used for improving temperature tolerance of electrode materials
CN106531991A
Negative electrode material for lithium ion power batteries and preparation method thereof
CN110459750A
Preparation method and application of chromium lithium titanate negative electrode material
CN113979475A
Preparation method of aluminum ion doped LiCrTiO4 with memory effect
CN115924972A
Preparation method of chromium lithium titanate
CN116153557A